Pepita Disco PPM : margins and elasticity - Hennessy, Julie; Meagher, Evan ([London] : SAGE, 2016)
Carolina Araujo had recently taken control of her family's business, Pepita Disco PPM, Uruguay's second-largest producer of beef-based dog food, treats, and toys. While she respected the company's nearly eighty-year history, Carolina felt that Pepita Disco had grown complacent with its market share and was basically preserving the status quo. Her plan was to re-energize the employee base and grow Pepita Disco's business faster than the overall market. This exercise poses a fictional problem about a company's efforts to predict the impacts of price, product cost, and spending moves on profitability.
Originally Published in: Hennessy, J., & Meagher, E. (2012). Pepita Disco PPM: Margins and Elasticity (Case revised 15/12/2014). 3-112-004. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Pepita Disco PPM; Accounting -- Case studies